2020
DOI: 10.1080/1750984x.2020.1846068
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and sense of coherence: a meta-analysis

Abstract: The salutogenic model of health proposes that sense of coherence, a multi-dimensional construct representing individuals' perceptions that their environment is comprehensible, manageable, and meaningful, is a key determinant of stress management and well-being.Generalized resistance resources such as preventive health orientation, material resources, and social support are proposed as determinants of sense of coherence. Health behaviors, particularly physical activity, are proposed as indicators of a preventiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 72 publications
1
5
0
Order By: Relevance
“…Unexpectedly, there were no significant associations between SOC and physical training (PT) and everyday PA, which is in line with some previous studies [13,19], but opposing to others that showed a positive association between PA and mental health [59,60]. The use of a single item (e.g., question) to assess adolescent PA and PT might be a possible explanation for the lack of association between PA, PT, and SOC.…”
Section: Determinants Of Sense Of Coherence (Soc)supporting
confidence: 56%
See 1 more Smart Citation
“…Unexpectedly, there were no significant associations between SOC and physical training (PT) and everyday PA, which is in line with some previous studies [13,19], but opposing to others that showed a positive association between PA and mental health [59,60]. The use of a single item (e.g., question) to assess adolescent PA and PT might be a possible explanation for the lack of association between PA, PT, and SOC.…”
Section: Determinants Of Sense Of Coherence (Soc)supporting
confidence: 56%
“…In general, SOC is a scale that measures how people use their generalized resistance resources (GRR) to deal with stress, as well as maintain and improve their health. Individuals with more available GRR (e.g., personal experience, self-esteem, money, social support, and intelligence) tend to do better coping with stressors and everyday life challenges [13]. SOC assesses three components: meaningfulness, comprehensibility, and manageability of life.…”
Section: Introductionmentioning
confidence: 99%
“…Among nurses, a mindfulness-based intervention did successfully enhance SOC [55]. Furthermore, physical activity has been associated with a stronger SOC [56]. These activities could also be carried out at home, in light of the restrictions imposed by the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…From a practical perspective, the findings inform mental health interventions of the need of improving the sense of coherence. For example, intervention studies have shown the effectiveness of regular participation in sports and healthy eating in building a strong sense of coherence [ 108 ]. Educators and clinicians may use the sense of coherence measures to screen for youth who may benefit from supportive interventions to strengthen their mental health [ 109 ].…”
Section: Limitations and Future Directionsmentioning
confidence: 99%